Zur Frage der meromorphen Lösungen mit defekten Werten von gewöhnlichen Differentialgleichungen erster Ordnung - Strelitz, S. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ш. И. Стрелиц. О дефектных значениях мероморфных решений обыкновенных дифференциальных уравнений первого порядкаŠ. Strelicas. Pirmos eilės paprastųjų diferencialinių lygčių meromorfinių sprendinių su defektinėmis reikšmėmis klausimu